Toxic epidermal necrolysis in a 5-year-old boy - case report - Pavan Puri; Sana Shaikh; Adesh Kakade; Rajiv Desai; Rahul Rahinj; Pankaj Shirsat (Brazilian Dental Science)
Toxic epidermal necrolysis (TEN) and Stevens-Johnson syndrome (SJS) are considered a spectrum of acute life-threatening mucocutaneous reaction that differ only in severity, often induced by drugs. Varicella-zoster virus has been rarely reported as an etiological agent in TEN. Our case report highlights the association of varicella-zoster virus and TEN in a 5-year-old boy.